Nano-Micro Letters - Zhang, Yafei
Nano-Micro Letters is a peer-reviewed, international, interdisciplinary and open-access journal published under the SpringerOpen brand that focus on science, experiments, engineering, technologies and applications of nano- or microscale structure and system in physics, chemistry, biology, material science, pharmacy and their expanding interfaces with at least one dimension ranging from a few sub-nanometers to a few hundreds of micrometers. Especially, emphasize the bottom-up approach in the length scale from nano to micro since the key for nanotechnology to reach industrial applications is to assemble, to modify, and to control nanostructure in micro scale. The aim is to provide a publishing platform crossing the boundaries, from nano to micro, and from science to technologies. Nano-Micro Letters publishes articles that focus on, but are not limited to, the following areas: - Synthesis, characterization, manipulation of nanomaterials - Quantum physics, nanoscale electrical transport - Nanoscale modeling and simulations - Microdevices based on nanomaterials or nanostructures - MEMS, NEMS - Nanosensors, Nanoelectronics, Nanomagnetics - Nano- or microfluids - Nanobiology, biotechnology, bioengineering - Nanomedicine - Solar cell based on nanostructures and nanomaterials - Applications related with nano- and micromaterials, devices and systems Article types - Papers. Reports of original research work; not normally more than 8500 words (10 journal pages). Papers on nano- and microscale theories, technologies, engineering and applications should include some representative results. Claims for originality or novelty of researches should be clearly stated in the abstracts. - Rapid communications. Brief, urgent announcements of significant advances or preliminary accounts of new work, not more than 3500 words (4 journal pages). The most important criteria for acceptance of a Rapid communication are novelty and significance. For these articles authors must state briefly, in a covering letter, exactly why their works merits rapid publication. - Review articles. These are intended to summarize accepted practice and report on recent progresses in selected areas. Such articles are generally commissioned from experts in various fields by the Editorial Board, but others wishing to write a Review article may submit an outline for preliminary consideration.